Gabapentin in chronic cough. (December 2015) - Gibson, Peter G.; Vertigan, Anne E.
Abstract: Background: Chronic cough is regarded as a challenging clinical problem due to its frequency and often limited therapeutic options. Chronic cough that remains refractory to usual medical treatment causes significant quality of life impairment. Methods: Recent developments in the treatment of cough include the use of speech pathology and pharmacotherapy with gabapentin. Relevant randomised control trials, reviews and case reports were identified through a PubMed and SCOPUS search of English-language literature referring to these concepts over the last eight years. Results: The effectiveness of neuromodulating medications such as gabapentin and pregabalin in the treatment of cough has been supported primarily through case series, case reports, prospective reviews and a double blind randomised controlled trial. Gabapentin results in a reduction in cough frequency and cough severity. It improves cough related quality of life. The effect is greatest in patients with features of central reflex sensitisation such as laryngeal paraesthesia, hypertussia and allotussia. These symptoms can be measured using the Newcastle Laryngeal Hypersensitivity Questionnaire. Side effects of gabapentin include somnolence and dizziness. Conclusion: Recent additions in the treatment of chronic cough have been significant as they consider cough to have a unifying diagnosis of cough hypersensitivity with or without the presence of a neuropathic basis. Effective treatments for refractory chronic cough that target these areas include behavioural treatment such as speech pathology and pharmaceutical treatment with neuromodulating medications such as gabapentin.